Home-prepared dog food: benefits and downsides - Ionică, Claudiu-Nicușor; Daina, Sorana; Pop, Romelia; Macri, Adrian (Frontiers in Animal Science, 2025)
Home-prepared diets for dogs, formulated by owners using conventional household ingredients, provide a distinctive means of managing canine nutrition. This method enables precise dietary adjustments tailored to an individual dog’s specific physiological and health requirements, often employing ingredients shared with human diets. For some owners, such diets are perceived as a natural and transparent alternative to commercial pet food, which is occasionally associated with potential long-term health risks. Despite the potential benefits of home-prepared diets, their formulation requires meticulous planning to ensure nutritional adequacy. Diets lacking input from nutrition experts may result in deficiencies or imbalances, posing significant health risks to dogs. This paper critically evaluates the advantages and limitations of home-prepared dog food, underscoring the necessity of professional oversight in developing nutritionally complete and safe feeding regimens.